Entrepreneurship - Zacharakis, Andrew; Corbett, Andrew C.; Bygrave, William D., 1937- (2020)
"The fifth edition has been thoroughly updated and enhanced throughout. We have developed a completely new chapter on business models, incorporating the Business Model Wheel. Angelo Santinelli, a former venture capitalist, entrepreneur and currently a startup advisor brings his 30 years of new venture experience and wrote the chapter on a new way to consider business models. We replaced half of the older cases. We have added cases on MightyWell, a medical apparel company looking to bring fashion to patients (Chapter 1), Vedaboo (Chapter 2) and iSlide (Chapter 3) which tracks product development in the sporting goods space, Gravyty, (Chapters 8 and 9) which shows a business planning process through the lens of artificial intelligence-based firm, Wefunder (Chapter 12) which looks at legal issues confronting crowdfunding, Esporte Interativo (Chapter 13) that illustrates a company striving to continue growth in a competitive industry and Inner City Weightlifting (Chapter 14) that highlights a social venture changing the lives of young men prone to gang activity"--
Includes bibliographical references and index.
Keywords: New business enterprises; Entrepreneurship; Small business -- Management